HERMENEUTIKA GADAMER DALAM STUDI TEOLOGI POLITIK - Attamimi, Faisal (State Institute of Islamic Studies (IAIN) Palu, 2012)
This article discusses Gadamer's hermeneutics in the study of political theology. The question of meaning is at the heart of hermeneutic study. The significance or meaning comes from the German word